Evaluation of Changes in Levels of Serum Selenium in Diabetic Pateints and in Diabetic Pateints with Cardiovascular Disease - Kasar, Khawla Abdul Kareem (Al-Nahrain Journal of Science, 2011)
Selenium, an essential micronutrient, may affect several cardiometabolic risk factors, such as glucose homeostasis and lipid concentrations. The aim of this study is to examin the relation between serum selenium concentrations with serum lipids in diabetic patients and in diabetic patients with cardiovascular diseases (CVD).A case control study conducted in the National Diabetes Center, College of Medicine at Al-Mustansiryia University. Fasting glucose, total cholesterol, high density lipoprotein–cholesterol (HDL-C), low density lipoprotein-cholesterol (LDL-C), and very low density lipoprotein-cholesterol (VLDL-C), HbA1c and Serum selenium were determine. Diabetes mellitus (n=256) divided into tow groups, group I (n=156) diabetic patients and group II (n=100) diabetic patients complicated with CVD. Normal healthy subjects were taken as control (n= 100).In the present study a significant decrease in selenium levels was found in patients groups compared to control also there is decrease in selenium levels of diabetic patients with CVD (group II) compared with diabetic patients (group I). These findings indicate that the decrease in serum selenium was associated with elevated serum concentrations of fasting blood glucose, total cholesterol, LDL-C, VLDL-C, triacylglycerols and duration of diabetes. In general despite their classification according to sex or diabetes type highly negative correlations (p<0.0001) were found with linear regression equations between fasting serum selenium concentration and HbA1c in patients group II. In conclusion the significant reductions in the level of selenium in diabetic patients may be response on the developing t he diabetic to anther disease like CVD.